2016
DOI: 10.4239/wjd.v7.i17.412
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and cognitive impairments

Abstract: There is strong evidence that diabetes mellitus increases the risk of cognitive impairment and dementia. Insulin signaling dysregulation and small vessel disease in the base of diabetes may be important contributing factors in Alzheimer's disease and vascular dementia pathogenesis, respectively. Optimal glycemic control in type 1 diabetes and identification of diabetic risk factors and prophylactic approach in type 2 diabetes are very important in the prevention of cognitive complications. In addition, hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
3
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(146 citation statements)
references
References 76 publications
2
119
3
22
Order By: Relevance
“…Compelling evidence suggests that insulin resistance and T2D worsen AD pathology and cognitive deficits (Haan, 2006; Ramos-Rodriguez et al, 2016; Saedi et al, 2016; Sena et al, 2015; Sheen and Sheu, 2016; Zilliox et al, 2016). To this end, central insulin signaling dysregulation has been demonstrated in post-mortem hippocampal and cortical samples from subjects with both mild cognitive impairment (MCI) and early AD (Talbot et al, 2012a; Watson and Craft, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence suggests that insulin resistance and T2D worsen AD pathology and cognitive deficits (Haan, 2006; Ramos-Rodriguez et al, 2016; Saedi et al, 2016; Sena et al, 2015; Sheen and Sheu, 2016; Zilliox et al, 2016). To this end, central insulin signaling dysregulation has been demonstrated in post-mortem hippocampal and cortical samples from subjects with both mild cognitive impairment (MCI) and early AD (Talbot et al, 2012a; Watson and Craft, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Both types of diabetes have been reported to be associated with the risk of dementia, although the odds of developing dementia remain modest again and causal-effect being not necessarily direct or independent [56]. For instance, an analysis of 28 studies showed a relative risk of dementia from insulin-dependent diabetes (IDD) of 1.7 (95% CI 1.6–1.8) which was lower for Alzheimer (1.5, 95% CI 1.4–1.7) [57].…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of the inflammatory process ends with an increase in the number of glial cells, microglia, and astrocytes, leading to dendritic atrophy and neuronal death (for a review see Flores, Flores-Gómez, et al, 2016), a process known as neurodegeneration (for review see Deleidi et al, 2015;Rawji et al, 2016). Accordingly, the anatomical and histological changes in the prefrontal cortex (PFC) and the hippocampus caused by chronic blood hyperglycemia lead to deficits in the cognitive process (for review see Hamed, 2017;Saedi et al, 2016), and reduced memory processing as a consequence of neurodegeneration (for review see Rojas-Gutierrez, et al, 2017).…”
Section: Animal Model In Dm S T Z-induced Hyperg Lycemia In R Atsmentioning
confidence: 99%